The Role of a Notary in Executing The Transfer of Land Rights That are Still Pledged to a Bank - Partogi Sitanggang, Frengki; Debora (Universitas Darussalam Gontor, 2024)
**English**Abstraction A notary is a public official with the authority to create genuine deeds, as stated in Article 1 Number 1 of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Notary Position. The genuine document itself, also known as a notary deed executed by or in front of a notary. The transfer of rights is one of the authentic deeds that a notary frequently creates at the appellant's request. For example, for deeds whose rights are certificates, there are usually deeds of agreement and binding sale and purchase. For the basis of rights that have been certified, the plaintiff must continue the process of changing the name of the certificate to the local land office using the Land Deed Making Officer (PPAT) product. One of the other authentic deed products that can be made by a Notary is the Credit Agreement Deed. This deed is a legal product that is generally encountered when someone wants to borrow money at the Bank. With the running of the process, there are many things happening in the field about debtors who default on their credit payments to banks so banks have to find ways how debtors can return the money that has been borrowed. One of them is by helping debtors sell collateral to parties who are willing to buy. **Indonesia**Merujuk pada Pasal 1 ayat 1 dari Undang-Undang Nomor 2 Tahun 2014, yang merupakan revisi dari Undang-Undang Nomor 30 Tahun 2004 mengenai Jabatan Notaris, dinyatakan bahwa notaris adalah pejabat umum yang memiliki kewenangan untuk menyusun akta autentik. Akta autentik, yang sering disebut sebagai akta notaris, adalah dokumen yang disusun oleh dan/atau di hadapan seorang notaris, yang memiliki kekuatan hukum yang mengikat. Salah satu Akta Autentik yang sering di buat oleh notaris atas permintaan penghadap adalah akta yang berhubungan dengan peralihan hak. Sebagai contoh untuk akta yang alas haknya merupakan sertifikat biasanya ada akta perjanjian dan pengikatan jual beli. Untuk alas hak yang sudah bersertifikat, penghadap harus melanjutkan proses balik nama sertfikat tersebut ke kantor pertanahan setempat dengan menggunakan produk Pejabat Pembuat Akta Tanah. Salah satu produk akta autentik lainnya yang dapat digarap Notaris adalah Akta Perjanjian Kredit. Akta ini merupakan produk hukum yang umumnya ditemui pada saat seseorang ingin meminjam uang di Bank. Dengan berjalannya proses tersebut, sangat banyak terjadi di lapangan tentang debitur yang ingkar dalam pembayaran kreditnya kepada bank sehingga bank harus mencari cara bagaimana debitur dapat mengembalikan uang yang telah dipinjam. Salah satunya adalah dengan cara membantu debitur menjual jaminan kepada pihak yang bersedia membeli.